Qualitative Analysis of Growth Parameters for PECVD Based Low Temperature Synthesis of Graphene Using Design of Experiments - Narula, Udit; Tan, Cher Ming (Frontiers in Materials, 2018)
Determination of key factors and parameters is necessary to design any process when number of factors are large. Design of Experiments technique is an important statistical tool to serve the purpose. This work demonstrates a method to perform qualitative analysis in order to determine cardinal control factors for Graphene growth at low temperature values using Fractional Factorial design. Graphene is synthesized using Plasma Enhanced Chemical Vapor Deposition (PECVD) method in this work. Attribute Response Analysis suggests that Graphene growth temperature, deposition time and RF power are important controlling factors. This is verified by Graphene growth using the predicted recipe.